(3b+2)(-7b-2)=0

Simple and best practice solution for (3b+2)(-7b-2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3b+2)(-7b-2)=0 equation:


Simplifying
(3b + 2)(-7b + -2) = 0

Reorder the terms:
(2 + 3b)(-7b + -2) = 0

Reorder the terms:
(2 + 3b)(-2 + -7b) = 0

Multiply (2 + 3b) * (-2 + -7b)
(2(-2 + -7b) + 3b * (-2 + -7b)) = 0
((-2 * 2 + -7b * 2) + 3b * (-2 + -7b)) = 0
((-4 + -14b) + 3b * (-2 + -7b)) = 0
(-4 + -14b + (-2 * 3b + -7b * 3b)) = 0
(-4 + -14b + (-6b + -21b2)) = 0

Combine like terms: -14b + -6b = -20b
(-4 + -20b + -21b2) = 0

Solving
-4 + -20b + -21b2 = 0

Solving for variable 'b'.

Factor out the Greatest Common Factor (GCF), '-1'.
-1(4 + 20b + 21b2) = 0

Factor a trinomial.
-1((2 + 3b)(2 + 7b)) = 0

Ignore the factor -1.

Subproblem 1

Set the factor '(2 + 3b)' equal to zero and attempt to solve: Simplifying 2 + 3b = 0 Solving 2 + 3b = 0 Move all terms containing b to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3b = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 3b = 0 + -2 3b = 0 + -2 Combine like terms: 0 + -2 = -2 3b = -2 Divide each side by '3'. b = -0.6666666667 Simplifying b = -0.6666666667

Subproblem 2

Set the factor '(2 + 7b)' equal to zero and attempt to solve: Simplifying 2 + 7b = 0 Solving 2 + 7b = 0 Move all terms containing b to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 7b = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 7b = 0 + -2 7b = 0 + -2 Combine like terms: 0 + -2 = -2 7b = -2 Divide each side by '7'. b = -0.2857142857 Simplifying b = -0.2857142857

Solution

b = {-0.6666666667, -0.2857142857}

See similar equations:

| 3/8=159/x | | 4x+2z=-4 | | 200-12a=644 | | 6m+16=8m-2 | | 4x+8=10x+33 | | 60+(3x-70)=180 | | (4y-3w)(3y-6w+7)=0 | | 10+2x=n | | 9+5x=104 | | (X+25)+3x=435 | | J-11/9=5 | | (a^3)+72=8 | | 14-3x=18-4x | | 9y+30+6+6y=13y-2y | | 7(x-2)-4(x+1)=-21 | | 6(2x-2)=45+5x | | 9y+3016+6y=13y-2y | | (v-2w-2)(v-4)=0 | | 2=200/w^2 | | 2x+8+x+1=0 | | 3(20x+50)=510 | | 5x+24(x-2)=184 | | -5x+40=6x-(70) | | 40x+7=40d+34 | | (27x^4)+3p=2p | | 2m+3=2m-3 | | 6r^3+2r^2-48r= | | 3y-7=80 | | H-3=12 | | (3v-w-2)(7v+6)=0 | | 4(x+2)+3(x-6)=-3 | | 5x-20=x-2.4 |

Equations solver categories